A facile technique for overcoming seeding barriers of hydrophobic polycaprolactone/hydroxyapatite-based nanofibers for bone tissue engineering - Tantri Liris Nareswari, Meta Juniatik, Aminatun Aminatun, Mona Sari, Ratna Annisa Utami, Yessie Widya Sari, Khairurrijal Khairurrijal, Yusril Yusuf, Tri Suciati (Journal of Applied Pharmaceutical Science, 2023)
Matrix hydrophobicity hinders cell attachment in tissue-engineered scaffolds. We proposed a facile seeding method to optimize cell presentation in nanofibrous mats formulated in a mixture of hydrophobic polycaprolactone (PCL), hydroxyapatite (HAp) mimicking bone surface roughness, and a ligand-supporting biopolymer. High-density osteoblast suspensions in serum-deficient media were seeded into composites arranged on a glass carrier sandwiched between cylindrical supports (seeding constructs) for 4 hours of initial seeding and subsequently statically cultured in a complete medium for 7 days. Cell behavior and growth were analyzed by viability assays, LIVE/DEAD fluorescence labeled imaging, and electron microscopy. The zeta potential and contact angle of PCL-HAp nanofibers were altered by the addition of biopolymers, which directed cell attachment and proliferation. Modified seeding proved the benefit of collagen reinforcement to mediate cell-matrix interactions, which was demonstrated by enhancing cell spread with nearly twofold substantial growth during culture. The addition of gelatin showed a lower level of increased cell adhesion than collagen. Interestingly, clusters of spheroid cells were found in the chitosan composite with high cell adhesion on the first day, but the cells did not grow further until the end of the culture. In contrast, poor cell adhesion and inconsistent growth were found after conventional seeding and thus emphasized the potential role of modified seeding in supporting matrix performance as a cell carrier.